2020
DOI: 10.1038/s41398-020-0745-6
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency neuronavigated rTMS effect on clinical symptoms and cognitive dysfunction: a pilot double-blind, randomized controlled study in Veterans with schizophrenia

Abstract: Cognitive impairment is a central aspect of schizophrenia (SCZ) that occurs at the onset of the disease and is related to poor social function and outcome in patients with SCZ. Recent literatures have revealed repetitive transcranial magnetic stimulation (rTMS) to be one of the efficient medical interventions for cognitive impairments. However, no study has been conducted to investigate the treatment effectiveness of 20 Hz rTMS with neuronavigation system administered to the left dorsolateral prefrontal cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 46 publications
0
27
1
1
Order By: Relevance
“…93,94 Furthermore, in recent years, the therapeutic potential of TMS for schizophrenia has also been investigated in academic centers. Although a number of clinical trials indicated moderate therapeutic effect for this disorder, 95,96 its clinical efficacy remains controversial yet. 97,98 Moreover, the neurobiological mechanisms of action remain unclear.…”
Section: Mri Scans For the Target Identification In Brain Stimulation Studiesmentioning
confidence: 99%
“…93,94 Furthermore, in recent years, the therapeutic potential of TMS for schizophrenia has also been investigated in academic centers. Although a number of clinical trials indicated moderate therapeutic effect for this disorder, 95,96 its clinical efficacy remains controversial yet. 97,98 Moreover, the neurobiological mechanisms of action remain unclear.…”
Section: Mri Scans For the Target Identification In Brain Stimulation Studiesmentioning
confidence: 99%
“…The shared and contradictory ndings of these studies show the sex differences in cognitive impairment of patients with rst-episode drug-naïve schizophrenia to worthy of further study. There are many explanations for these differences, most of which are related to genetic susceptibility and neurodevelopment, or bio-psycho-social factors [19][20][21][22]. In addition, culture may also play an important role in sex differences in schizophrenia [2,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…An early study found that both 10 and 20 Hz rTMS improved memory in patients with schizophrenia, while another study found that both 10 and 20 Hz rTMS had delayed effects on cognitive function at the 6-month follow-up (55). Guan et al also found the effectiveness of high-frequency rTMS stimulation in improving the cognitive function of patients with schizophrenia (56). A recent meta-analysis also found that 10 Hz rTMS over the DLPFC significantly improved all indicators of working memory performance, including reaction time and accuracy (57).…”
Section: Discussionmentioning
confidence: 93%